STRATEGI EFEKTIF DALAM BIMBINGAN KONSELING UNTUK MENINGKATKAN MOTIVASI BELAJAR DEMI MENCAPAI KEMANDIRIAN BELAJAR - Nazwa Nazwa; Aulia Syahrani Raidila; Gusman Lesmana (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Guidance is support or assistancegiven to a person or group of people to help them avoid or overcome life difficulties, so that they can achieve well-being in life. or overcome life difficulties, so that they can achieve well-being in their lives. their lives. The writing of this article uses qualitative research with literature studies. This research is a research method that collects some information. Effective learning methods provided by counseling guidance teachers are tutoring that can overcome various difficulties related to the demands of school or other education at school or others. High learning motivation is an important key in building learning independence in students. In facing problems, they often depend on others to find solutions. Based on the explanation above, then the author can conclude that counseling strategies using learning guidance can help individuals increase learning motivation is proven to be effective in achieving the learning independence needed to achieve their academic goals. necessary to achieve their academic goals.